Epidemiology of high-risk human papillomavirus and cervical lesions in African women living with HIV/AIDS: effect of anti-retroviral therapy. (14th January 2017) - Kelly, Helen A.; Sawadogo, Bernard; Chikandiwa, Admire; Segondy, Michel; Gilham, Clare; Lompo, Olga; Omar, Tanvier; Didelot, Marie-Noelle; Nagot, Nicolas; Meda, Nicolas; Weiss, Helen A.; Delany-Moretlwe, Sinead; et al.
Abstract : Objective: To describe the effect of antiretroviral therapy (ART) and HIV-related factors on high-risk human papillomavirus (HR-HPV) and high-grade cervical intraepithelial neoplasia lesions (CIN2+) among women living with HIV/AIDS (WLHA) in sub-Saharan Africa. Design: Prospective cohort of WLHA in Ouagadougou, Burkina Faso (BF) and Johannesburg, South Africa (SA). Recruitment was stratified by ART status. Methods: At baseline and endline (median 16 months), cervical samples, and biopsies were analyzed for HPV genotyping (InnoLiPA) and by histology. Logistic regression was used to estimate associations of ART and HIV-related factors with HR-HPV and CIN2+ outcomes, and all results presented are adjusted for baseline CD4 + cell count. Results: Among 1238 enrolled WLHA (BF = 615; SA = 623), HR-HPV prevalence was 59.1% in BF and 79.1% in SA. CIN2+ prevalence was 5.8% in BF and 22.5% in SA. Compared with long-duration ART users (>2 years), HR-HPV prevalence was higher among short-duration ART users [≤2 years; adjusted prevalence ratio (aPR) = 1.24, 95% confidence interval (CI) 1.04–1.47] in BF, and CIN2+ prevalence was higher among short-duration ART users [adjusted odds ratio (aOR) = 1.99, 95% CI 1.12–3.54) and ART-naive participants (aOR = 1.87, 95% CI 1.11–3.17) in SA. Among 963 (77.8%) women seen at endline, HR-HPV persistence was 41.1% in BF and 30.2% in SA; CIN2+ incidence over 16-months was 1.2% in BF and 5.8% in SA. HR-HPV persistence was associated with being ART-naive in BF (aPR = 1.89, 95% CI 1.26–2.83), and with short-duration ART use (aPR = 1.78, 95% CI 1.11–2.86) and HIV-1 plasma viral load at least 1000 copies/ml (aPR = 2.87, 95% CI 1.63–5.05) in SA. CIN2+ incidence was reduced among women on ART in SA (aOR = 0.39, 95% CI 0.15–1.01). Conclusion: Prolonged and effective ART is important in controlling HR-HPV and the development of CIN2+.